2020
DOI: 10.1519/jsc.0000000000003493
|View full text |Cite
|
Sign up to set email alerts
|

Complex and Contrast Training: Does Strength and Power Training Sequence Affect Performance-Based Adaptations in Team Sports? A Systematic Review and Meta-analysis

Abstract: Cormier, P, Freitas, TT, Rubio-Arias, JÁ, and Alcaraz, PE. Complex and contrast training: Does strength and power training sequence affect performance-based adaptations in team sports? A systematic review and meta-analysis. J Strength Cond Res 34(5): 1461–1479, 2020—The aims of this meta-analysis were to examine the effects of 2 different strength and power training sequences (complex: CPX; and contrast: CNT, training) on performance-based adaptations in team sports {lower-body strength (1 repetition maximum [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
96
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(106 citation statements)
references
References 68 publications
7
96
0
3
Order By: Relevance
“…For instance, while this training approach is theoretically based on an expected PAPE effect of the heavy loads on the lighter loads of biomechanical similarity, it appears that these 2 assumptions are false since (1) there are no studies systematically reporting the PAPE effects during each session of the examined interventions; (2) there is no evidence on the superiority of biomechanically similar exercises for PAPE [7]. Further, the use of complex training approaches does not seem to be better than the use of contrast training, which consists of performing first all the heavy loads and subsequently the lighter loads at the end of the training session [60]. This point is important as it suggests that the effectiveness of these approaches may be more based on the combination of different stimuli, independently of the order, than on the use of a single stimulus for training adaptations [61].…”
Section: Complex Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, while this training approach is theoretically based on an expected PAPE effect of the heavy loads on the lighter loads of biomechanical similarity, it appears that these 2 assumptions are false since (1) there are no studies systematically reporting the PAPE effects during each session of the examined interventions; (2) there is no evidence on the superiority of biomechanically similar exercises for PAPE [7]. Further, the use of complex training approaches does not seem to be better than the use of contrast training, which consists of performing first all the heavy loads and subsequently the lighter loads at the end of the training session [60]. This point is important as it suggests that the effectiveness of these approaches may be more based on the combination of different stimuli, independently of the order, than on the use of a single stimulus for training adaptations [61].…”
Section: Complex Trainingmentioning
confidence: 99%
“…The use of heavy loads before lighter loads of biomechanical similarity is known as complex training [60]. recent reviews and meta-analyses have confirmed the long-term effectiveness of this approach for the enhancement of specific sport tasks, such as jumping and sprinting [60][61][62]. However, there are a number of issues to be considered before implementation.…”
Section: Complex Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last four decades (Fleck and Kontor, 1986), a considerable amount of published studies have analyzed the effects of CT on athletes' physical fitness and some metaanalyses have attempted to congregate the extant literature (Freitas et al, 2017;Bauer et al, 2019;Cormier et al, 2020;Pagaduan and Pojskic, 2020). Some meta-analyses have also been conducted specifically on team sports athletes (Freitas et al, 2017;Cormier et al, 2020). However, these studies included athletes with different sporting backgrounds (i.e., soccer, futsal, basketball, volleyball, rugby, football, water polo, track and field, and handball), potentially biasing the results for a particular sport, such as soccer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to clarify the specific effects of CT (and its moderators; e.g., programme duration) on soccer player's physical fitness performance, the aim of this meta-analysis was to evaluate the effects of CT interventions on sprint, jump, and COD ability among soccer players. With reference to previous studies (Freitas et al, 2017;Kobal et al, 2017;Bauer et al, 2019;Cormier et al, 2020), we hypothesized that CT would be effective in improving soccer players' physical fitness, with greater effects observed as compared to a control condition. Accordingly, our research question was: what are the effects of CT interventions (and its moderators) on sprint, jump, and COD ability among soccer players when compared to a control group?…”
Section: Introductionmentioning
confidence: 99%